Characterization, water retention and availability of different types of biochar from animal and plant origin (Research, Society and Development, 2022)
The increase in food production to meet global demand has generated a large volume of organic waste. When reinserted into the production chain, this waste can provide various environmental services, mainly not referring to the quality and quantity of two water resources. The biocarvão presents great potential as a solo corrector, source of nutrients, and conditioner, increasing water retention. This study produced and characterized biochars from six types of biomass (sugar cane bagasse-SBB, dry coconut husks-DCB, green coconut husks-GCB, sludge sludge-SSB, corn cobs-CCB, and orange bagasse- OBB). The main objective was to assess the water retention of biochar. The biochar was produced through slow pyrolysis at a temperature of 550ºC, ground and penetrated to determine porosity, specific surface area, electrical conductivity, pH, cation exchange capacity, morphology structural, immediate and elemental analysis, particle size distribution, water retention capacity (WRC), retention curve and available water (AW). All biochars presented great variability in their characteristics. A WRC varied from 88% to 628 % as follows: SSB < OBB < GCB < CCB = DCB < SBB A AW varied from 10% to 140% where SBB > DCB > CCB = GCB > OBB > SSB. Hence, SBB showed higher water retention, and SSB was the least efficient.